(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
The integration of digital technologies into education has significantly transformed modern teaching and learning processes. One of the most promising approaches in this field is gamification, which involves the use of game elements in non-game contexts to enhance learner motivation and engagement. This study explores the role of gamification in digital learning environments for teaching English as a foreign language. The research investigates how gamified activities, including points, badges, leaderboards, and interactive tasks, influence students’ motivation and language skill development. The study was conducted with a group of English language learners using various digital platforms.